1991
DOI: 10.1161/01.str.22.12.1548
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical analysis of focal ischemia in rats.

Abstract: Background and Purpose: Increases in uric acid follow experimental stroke, which may be related to free radical formation by xanthine oxidase. The present study examined the time course of changes in xanthine and uric acid and their relationship to changes in the free radical scavengers glutathione, cysteine, and ascorbic acid.Methods: Focal ischemia was induced by occluding the middle cerebral artery, followed by transient occlusion of the common carotid arteries for 60 minutes. At varying time points, animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(68 citation statements)
references
References 35 publications
5
63
0
Order By: Relevance
“…4 These increments have been attributed to the conversion of XDH to XO within the ischemic tissue 25,26 or within endothelial cells. 27 Uric acid also protected cultured rat hippocampal neurons against cell death induced by glutamate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 These increments have been attributed to the conversion of XDH to XO within the ischemic tissue 25,26 or within endothelial cells. 27 Uric acid also protected cultured rat hippocampal neurons against cell death induced by glutamate.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia also promotes the conversion of xanthine dehydrogenase (XDH) to xanthine oxidase (XO), as the likely result of increased intracellular calcium, and activation of proteases. 3,4 Whereas XDH activity does not produce reactive oxygen species, the XO reaction is a major source of free radicals during ischemia/reperfusion injury. 5 Arguing for a role of XO in brain damage are studies in which allopurinol, a XO inhibitor, has been shown to have protective effects against reperfusion injury.…”
mentioning
confidence: 99%
“…GUO presents neuroprotective effect in in vivo and in vitro experimental models of brain diseases associated with glutamatergic excitotoxicity [11,12]. It was showed that after focal stroke in rats, GUO levels are elevated within 2 h and remain high for 7 days in the brain tissue [13]. In oxygen/glucose deprivation (OGD) protocol, an in vitro model for ischemia, we showed that GUO is protective by improving extracellular glutamate uptake [14].…”
Section: Introductionmentioning
confidence: 95%
“…However, in most cases data linking the GSH system to these disorders were derived from tissue homogenates, which cannot detect cellular heterogeneity. It is possible that these limitations may have contributed to contrary reports on how the GSH levels change during some neurological diseases (75)(76)(77)(78). Our approach can be applied to animal models of disease and mouse mutants with abnormal handling of oxidative stress (79,80) to measure GSH levels in different brain regions directly.…”
Section: Mcb Labeling With Two-photon Microscopy Resolves Cellular Gsmentioning
confidence: 99%